WEB DESIGN APPLICATIONS FOR HELMET MARKETING SALES IN HELMET STORE WITH PHP, MYSQL, AND MACROMEDIA DREAMWEAVER 8.0 - Zacky Affandi; Eriek Orlando (Jurnal Sistem Informasi, 2010)
Along with the rapid develeopment in information technology, make everyperson getting information easier. The Internet is a fast and easy way to conveythat information to reach the wider community. The use of website is veryuseful for promoting, offering and informing the sales of helmet for theconsumers in Helmet Store. Everything is presented in a web page display thatis easily understood by consumers, ranging from the main menu to the specificsearching of helmet based on brand, type and price of these helmets.Macromedia Dreamweaver 8.0, PHP and MySQL are a few examples of themany software tools that can solve the problem